2008
DOI: 10.1007/s11368-008-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of iron-rich, tropical soil organic carbon pools after land-use change from forest to sugarcane

Abstract: Background, aim, and scope Land-use change can significantly influence carbon (C) storage and fluxes in terrestrial ecosystems. Soil-plant systems can act as sinks or sources of atmospheric CO 2 depending on formation and decomposition rates of soil organic matter. Therefore, changes in tropical soil C pools could have significant impacts on the global C cycle. This study aims to evaluate the impacts of long-term sugarcane cultivation on soil aggregation and organic matter, and to quantify temporal dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Therefore, soil C dynamics, such as C sequestration and mineralization, and soil respiration, play the most important role in the carbon cycle of terrestrial ecosystems (Raich and Schlesinger, 1992;Deng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, soil C dynamics, such as C sequestration and mineralization, and soil respiration, play the most important role in the carbon cycle of terrestrial ecosystems (Raich and Schlesinger, 1992;Deng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dynamics in the soil play the most important role in the carbon cycle of terrestrial ecosystems (Raich and Schlesinger 1992;Deng et al 2009;Xu et al 2009). However, there are relatively few studies on the effect of forest soil respiration on the carbon cycle (Schinel 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al (2009) highlighted the role of iron in the formation of microaggregates in tropical soils and present results by which the authors demonstrate that in soil with 56 years of sugar cane cultivation, despite the great loss in OC, there is only a small diminution in the macroaggregate fraction.…”
Section: Resultsmentioning
confidence: 55%
“…Lal et al (2007) proposed that in the majority of soils worldwide, carbon loss, due to land-use changes, is found to be between 30 and 75 %. Additionally, for tropical soils, in the Hainan Province, China, Deng et al (2009) found that under sugar cane cultivation over a period of 56 years, the soil lost > 60 % in OC-stock in the soil under the secondary forest.…”
Section: Resultsmentioning
confidence: 99%